Endophytic Streptomyces sp. NEAU-ZSY13 from the leaf of Perilla frutescens, as a promising broad-spectrum biocontrol agent against soil-borne diseases - Wang, Zhiyan; Gao, Congting; Yang, Jingquan; Du, Rui; Zeng, Fanli; Bing, Hui; Xia, Banghua; Shen, Yue; Liu, Chongxi (Frontiers in Microbiology, 2023)
Soil-borne diseases cause significant economic losses in global agricultural production. These diseases are challenging to control due to the invasion of multiple pathogens into host plants, and traditional chemical control methods often yield unsatisfactory results. In this study, we isolated and identified an endophytic Streptomyces, designated as NEAU-ZSY13, from the leaf of Perilla frutescens. This isolate exhibited broad-spectrum antifungal activity against 17 soil-borne phytopathogenic fungi, with Bipolaris sorokiniana being the most prominent. Additionally, it displayed strong antibacterial activity against the soil-borne phytopathogenic bacterium Ralstonia solanacearum. To assess its biocontrol potential, the isolate was utilized to produce a biofertilizer through solid-state fermentation. The fermentation conditions were optimized using response surface methodology to maximize the spore production. The results revealed that more abundant spores were produced with a 1:2 ratio of vermicompost to wheat bran, 60% water content, 20% inoculation amount and 28 °C. Subsequent pot experiments demonstrated that the application of the biofertilizer with a spore concentration of 10 8 CFU/g soil effectively suppressed the occurrence of tomato bacterial wilt caused by R. solanacearum and wheat root rot caused by B. sorokiniana, with biocontrol efficacies of 72.2% and 78.3%, respectively. Chemical analysis of NEAU-ZSY13 extracts, using nuclear magnetic resonance spectrometry and mass analysis, identified niphimycin C and niphimycin A as the primary active constituents. These compounds exhibited high activity against R. solanacearum (EC50 of 3.6 and 2.4 µg mL -1 ) and B. sorokiniana (EC50 of 3.9 and 3.4 µg mL -1 ). In conclusion, this study demonstrates the potential of Streptomyces sp. NEAU-ZSY13 as a biofertilizer for the control of soil-borne diseases.